2019
DOI: 10.1088/1748-9326/ab1542
|View full text |Cite
|
Sign up to set email alerts
|

Modelling public health improvements as a result of air pollution control policies in the UK over four decades—1970 to 2010

Abstract: In much of the industrialised world, policy interventions to address the challenges of wide-spread air pollution as resulting from development and economic progress in the 2nd half of the 20th century have overall led to reductions in air pollution levels and related health effects since the 1970s. While overall improvements towards reducing health effects from ambient air pollution are recorded, comprehensive and consistent assessments of the long-term impact of policy interventions are still scarce. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 31 publications
0
39
0
1
Order By: Relevance
“…However, Poland presently does not have a problem in exceeding its thresholds [37]. A study from the United Kingdom shows that this might increase premature deaths from ozone as well as decrease the numbers attributed to PM 2.5 [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…However, Poland presently does not have a problem in exceeding its thresholds [37]. A study from the United Kingdom shows that this might increase premature deaths from ozone as well as decrease the numbers attributed to PM 2.5 [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Its presence in the atmosphere is one of the major environmental concerns, since it contributes to acid rain formation [4,5], has various other environmental impacts such as localised cooling (by 2 of 19 reflecting sunlight back into space) [6] and is hazardous to human health resulting in many types of respiratory illnesses such as asthma and bronchitis [7,8]. The emission of SO 2 by industrial activities also needs to be limited.…”
Section: An Overiew Of the Sulphur Problemmentioning
confidence: 99%
“…the Gothenburg protocol (UNECE, 1979) and the European Directive on National Emission Ceilings (EC, 2016), have been effective and efficient in improving air quality at national and local level. Several European studies 40 addressed this topic, focussing on the entire continent (Colette et al, 2011(Colette et al, , 2017aWilson et al, 2012;Guerreiro et al, 2014;Yan et al, 2018) and on single countries (Sicard et al, 2009;Cattani et al, 2014;Querol et al, 2014;Carnell et al, 2019;Velders et al, 2020). The studies were carried out using observed and/or modelled concentrations.…”
Section: Introductionmentioning
confidence: 99%